The European Network Against Racism (ENAR) as NGO Against Islamophobia in France - ILMISANI, Radendy Ahmad; JUNED, Mansur (Journal of Tourism Economics and Policy, 2024)
This research, will explain about the relationship between the European Network Against Racism (ENAR) and Islamophobia in France. The increasing Muslim population in France over the years, driven by globalization and immigration, is a significant aspect to consider. While their freedoms should be preserved, the challenging reality in France is the difficulty in upholding these rights due to Islamophobia within the majority of the French population and institutional racism (with France Laïcité) that diminishes their chances of obtaining their rights. Therefore, employing a case study data collection technique, this study will explore how ENAR, as a Non-Governmental Organization, takes action to address this issue through projects such as "Muslim Women, Forgotten Women?," collaborations with like-minded NGOs, and partnerships with the European Union, a key decision-maker. Through the analysis of these projects, the author aims to examine ENAR's efforts in combating Islamophobia in Europe and to understand why ENAR may be less effective in addressing Islamophobia specifically in France. With this the Author bring the question "Has The European Network Against Racism (ENAR) been successful in preventing and eliminating Islamophobia in France?"